Current Evidence on Cell Death in Preterm Brain Injury in Human and Preclinical Models - Truttmann, Anita C.; Ginet, Vanessa; Puyal, Julien (Frontiers in Cell and Developmental Biology, 2020)
Despite tremendous advances in neonatal intensive care, prematurity nowadays carries a high burden of neurological morbidity lasting lifelong. Preterm brain injury, covered by the term encephalopathy of prematurity (EoP), associates white matter injury and inflammation, but more and more evidence implicates also gray matter damage and excitotoxicity. Understanding the way cells are damaged is crucial to design brain protective strategies and in this purpose preclinical models largely contribute to improve the comprehension of the cell death mechanisms. While neuronal cell death has been deeply investigated and characterized in (hypoxic-ischemic) encephalopathy of the newborn at term, little is known about the types of cell death occurring in EoP. Three main different morphological cell death types are observed in the immature brain, specifically in models of hypoxic-ischemic encephalopathy, namely necrotic, apoptotic and autophagic cell death. Features of all three types may be present in the same dying neuron. In preterm brain injury, description of cell death types is sparse, and cell loss concern primarily immature oligodendrocytes and infrequently neurons. In the present review, we first shortly discuss the different main preterm brain injury conditions including periventricular leucomalacia (PVL), diffuse white matter injury (dWMI) and intraventricular hemorrhages as well as potentially harmful iatrogenic conditions linked to premature birth. Then, we present an overview of current evidences concerning cell death in both clinical human tissue data and preclinical models. We conclude that, to improve brain protective strategies, not only apoptosis but also other cell death (such as regulated necrotic and autophagic) pathways have now to be investigated together in order to consider all cell death mechanisms involved in the pathogenesis of preterm brain damage.